Effects of rhythmic auditory stimulation on motor function and balance ability in stroke: A systematic review and meta-analysis of clinical randomized controlled studies - Lei Wang; Jin-lin Peng; Wu Xiang; Yi-jie Huang; Ai-lian Chen (Frontiers in Neuroscience, 2022)
ObjectiveRhythmic auditory stimulation (RAS) belongs to neurologic music therapy, which has attracted clinical attention because of its efficacy in motor function after stroke. This study aimed to summarize the effectiveness of rhythmic auditory stimulation (RAS) for the treatment of motor function and balance ability in stroke through a systematic review and meta-analysis.MethodsAll studies were retrieved from six databases. The effects of RAS on stroke were determined using the following indicators: motor function including step length, step cadence, velocity, Fugl–Meyer assessment (FMA); and balance ability including overall balance index (OBI) and Berg Balance Scale (BBS). The risk map of bias of the quality of the studies and the meta-analysis results of the indicators was prepared using RevMan 5.2 software.ResultsA total of 1,363 abstracts were retrieved. Among them, 325 duplicate studies were eliminated, and 971 studies were excluded after reading the titles and abstracts. In addition, by downloading the full text for further reading and screening, 47 studies were excluded. A total of 22 studies were included in the systematic review, and 18 studies were included in the meta-analysis. Assessment of quality, based on the PEDro scale, two studies had low quality, three studies had excellent quality, and the other studies had good quality; based on the Cochrane Collaborative Network Bias Risk Assessment Scale. A total of 15 studies specifically explained the random methods used. Meanwhile, seven studies did not report random sequence generation. A total of 10 studies reported that the evaluation of experimental results was blinded. In the meta-analysis, the results of motor function [namely, velocity (SMD = 0.99, 95% CI (0.43, 1.55)), step length (SMD = 0.97, 95% CI (0.74, 1.20)), and step cadence (MD = 5.16, 95% CI (4.17, 6.14)), FMA (MD = 2.93, 95% CI (2.04, 3.83))], were statistically significant (P < 0.01). The results of balance ability [OBI (MD = −0.51, 95% CI (−0.86, −0.16)) and BBS (MD = 2.93, 95% CI (1.67, 4.20))], were also statistically significant (P < 0.01). Among all the outcome indicators, three indicators were included in more than 10 studies: these are step length, step cadence, and velocity. The results showed that the two sides of the funnel chart were asymmetrical, thus these results all showed heterogeneity. The GRADEpro GDT online tool was used to evaluate the quality of evidence for the outcome indicators in the included studies. Five outcome indicators were included, of which three were low-quality indicators and two were moderate-quality indicators.ConclusionsRAS could improve gait parameters, walking function, and balance ability of individuals with stroke. However, studies or samples of outcome indicators for balance ability of stroke patients is relatively insufficient, which also requires further research in the future.Systematic review registrationPROSPERO, identifier: CRD42021225102.